Pharmacokinetics of ferric bepectate—a new intravenous iron drug for treating iron deficiency. Issue 2 (3rd April 2019) - Muñoz, Manuel; Olsen, Peter Skov; Petersen, Tonny Studsgaard; Manhart, Susanne; Waldorff, Stig
Abstract: IV iron is indicated in clinical conditions, where rapid anaemia alleviation and repletion of iron stores are required. The acute toxicity of IV iron is ascribed to the presence of labile iron in plasma. Thus, shorter plasma residence time might improve the safety profile, even for compounds holding‐on the iron tightly. In this single‐centre, open‐label, single‐dose escalation study, we evaluated the elimination kinetics of ferric bepectate (FBP) compared to those of ferric carboxymaltose (FCM). Thirty‐three iron‐depleted anaemic patients who had undergone cardiac surgery were included and received 200, 500 or 1500 mg FBP or 500 mg FCM. Plasma drug curves were subjected to model‐free analysis. Because saturation kinetics was found, a compartmental model with limited elimination capacity was applied. Urinary iron excretion was also analysed. The initial non‐compartmental analysis revealed an increasing AUC/dose ratio for FBP. For both drugs, the central distribution compartment corresponded to plasma volume, and elimination followed Michaelis‐Menten saturation kinetics. Maximal elimination rates ( V max ) were 224 mg/h and 81 mg/h for FBP 500 mg and FCM 500 mg, respectively; drug concentrations at half V max ( K m ), 99 mg/L and 212 mg/L, respectively; and terminal plasma half‐life (T½), 3.05 h and 8.96 h, respectively. Both drugs were equally effective in eliciting an early ferritin rise. Urinary iron excretion was measurable in all patients receiving FCM but not in those receiving FBP, which was well tolerated. Intravenous iron drugs are subject to capacity‐limited elimination with different saturation thresholds. Urinary iron excretion can be used as a surrogate for labile plasma iron.